2011
DOI: 10.1523/jneurosci.3384-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Use Dependence of Presynaptic Tenacity

Abstract: Recent studies indicate that synaptic vesicles (SVs) are continuously interchanged among nearby synapses at very significant rates. These dynamics and the lack of obvious barriers confining synaptic vesicles to specific synapses would seem to challenge the ability of synapses to maintain a constant amount of synaptic vesicles over prolonged time scales. Moreover, the extensive mobilization of synaptic vesicles associated with presynaptic activity might be expected to intensify this challenge. Here we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 66 publications
2
32
0
Order By: Relevance
“…These data are in accordance with the finding that electrical stimulation has no influence on the mobility of single SVs in short timeframes (Kamin et al, 2010), although a more careful evaluation with longer timeframes and/or stimulation protocols might be required, because this issue is still debated (Fisher-Lavie et al, 2011). Nevertheless, our results indicate that the population of delocalized SVs observed in TKO synapses includes exocytosis-competent SVs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are in accordance with the finding that electrical stimulation has no influence on the mobility of single SVs in short timeframes (Kamin et al, 2010), although a more careful evaluation with longer timeframes and/or stimulation protocols might be required, because this issue is still debated (Fisher-Lavie et al, 2011). Nevertheless, our results indicate that the population of delocalized SVs observed in TKO synapses includes exocytosis-competent SVs.…”
Section: Discussionsupporting
confidence: 92%
“…Very recent findings render this result particularly relevant because SV redistribution within the same axon might be essential for the competitive strengthening/weakening of presynaptic efficacy and might improve pattern discrimination in dendritic networks (Herzog et al, 2011;Padamsey and Jeans, 2012). Through the mobilization/immobilization of SVs, Syns might locally regulate the plastic properties at single presynapses both acting as restrictors, by contributing with a resilient force to the tenacity of the terminal (Fisher-Lavie et al, 2011) and serving as integrators of presynaptic signaling in a phosphorylation-dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore conceivable that because of internal gradients, the properties of presynaptic boutons may differ. Thus, the unequal distribution of organelles and molecules along a single neurite could account for the findings presented here (Fisher-Lavie et al, 2011). …”
Section: Discussionsupporting
confidence: 66%
“…Initially, we verified that EGFP-fusion proteins of Bassoon, ELKS2, Munc13-1, and SV2 were appropriately localized within presynaptic boutons of synapses formed between neurons after 14 DIV (Bresler et al, 2004;Fisher-Lavie et al 2011; data not shown). These data indicate that the EGFP tags do not interfere with synaptic delivery.…”
Section: Elks2 But Not Munc13-1 Traffics Into the Axon In Associatimentioning
confidence: 85%